A critical discourse analysis of twitter posts during the Sheraton move: a case study of the online public sphere in Malaysia - Davadason Peter, Abszra (2025)
My thesis is a study of Malaysian political communication on Twitter by political elites, media organisations, and societal users. Using the Sheraton Move as a case study, I deconstruct 102 872 tweets during the period which witnessed Pakatan Harapan losing its hard-fought victory of the 14th General Elections in 2018. An exploration of literature showed that research of the effect of Twitter usage remain fragmented. Against the theoretical backdrop of Habermas’ public sphere, I propose a framework to better understand the Malaysian Twittersphere. For this, I divide the Malaysian Twittersphere into three communicative levels: the structural, representational, and interactional. I used a mixed method approach that combined critical discourse analysis of expert interviews, focus group discussion of users, archival research with quantitative content analytics to examine the reactions during the Sheraton Move on Twitter.